(untitled) (Revista de Ciências Agroveterinárias, 2022)
The humid tropics harbor great biological diversity, in addition to native species with forage potential as alternatives for animal feed. However, using trees and shrubs and having plantations are limited by the absence of information on their growth and seed germination. Therefore, the goal was to evaluate the germination capacity of native plant species with forage potential in tropical rainforest conditions, selecting eight species with important nutritional value: Bauhinia tarapotensis, Crescentia cujete, Zygia longifolia, Cecropia ficifolia, Piptocoma discolor, Piper bredemeyeri, Calathea lutea and Heliconia rostrata. Two treatments were evaluated: T1: Seeds (sexual and asexual) immersed for 12 hours in water, and T2: Seeds (sexual and asexual) without any pre-germination treatment (control). Significant differences were found in the germination percentage among species, treatments and the interaction of the two factors (p < 0.01). The species C. cujete, C. ficifolia and P. discolor presented better germination percentages with T1, in contrast to P. bredemeyeri, which adapted better to T2. In the same sense, H. rostrata (93%), C. cujete (91%) and Z. longifolia (89%) with T1, were the species with the highest germination capacity when compared to the other species, being desirable for use as fodder in agricultural production systems, due to their high germination power. In general, the pre-germinative treatment with water was very effective in increasing the permeability of the seed coat and, therefore, favored the breaking of endogenous physiological dormancy.